2019
DOI: 10.26499/li.v36i1.71
|View full text |Cite
|
Sign up to set email alerts
|

Working With a Linguistic Corpus Using R: An Introductory Note With Indonesian Negating Construction

Abstract: This paper demonstrates the use of R for a unified data science in corpus linguistics via a series of corpus-based analyses on Indonesian Negating Construction. The data is based on c17-million word-tokens of an online-news corpus, a part of the Indonesian Leipzig Corpora. We identified that tidak is the most frequent form in our corpus. Next, we found that tak has significantly higher type frequency for negated-predicates with [ter-X-kan] schema compared to tidak; this finding provides a quantitative nuance a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…Conceptualizations of human emotions have been a research topic of great interest in linguistics, for there have been many studies on various emotion concepts, such as ANGER (Glynn, 2014;Kahumburu, 2016;Yu, 1995), FEAR (Caballero & Díaz-Vera, 2021;Oster, 2010Oster, , 2012, HAPPINESS (Nguyen, 2016;Rajeg, 2019;Stefanowitsch, 2004), JEALOUSY (Díaz-Vera & Caballero, 2013;Ogarkova, 2007), LOVE (Gawda, 2019;Glynn, 2002), PRIDE (Soares da Silva, 2020), SADNESS (Verdaguer & Castaño, 2018), and SHAME (Krawczak, 2014a(Krawczak, , 2014b(Krawczak, , 2018. These studies have revealed that, in contemporary language use, human emotions are often understood or conceptualized in metaphorical terms (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conceptualizations of human emotions have been a research topic of great interest in linguistics, for there have been many studies on various emotion concepts, such as ANGER (Glynn, 2014;Kahumburu, 2016;Yu, 1995), FEAR (Caballero & Díaz-Vera, 2021;Oster, 2010Oster, , 2012, HAPPINESS (Nguyen, 2016;Rajeg, 2019;Stefanowitsch, 2004), JEALOUSY (Díaz-Vera & Caballero, 2013;Ogarkova, 2007), LOVE (Gawda, 2019;Glynn, 2002), PRIDE (Soares da Silva, 2020), SADNESS (Verdaguer & Castaño, 2018), and SHAME (Krawczak, 2014a(Krawczak, , 2014b(Krawczak, , 2018. These studies have revealed that, in contemporary language use, human emotions are often understood or conceptualized in metaphorical terms (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have revealed that, in contemporary language use, human emotions are often understood or conceptualized in metaphorical terms (e.g. Díaz-Vera & Caballero, 2013;Kahumburu, 2016;Ogarkova, 2007;Rajeg, 2019). Their findings highlight the importance of metaphor in human thought and language, although, in historical language use, expressions of emotions have been found to be largely literal in some research (e.g.…”
Section: Introductionmentioning
confidence: 99%